Computational Reproducibility of "The Impact of Presidential Appointment of Judges: Montesquieu or the Federalists?" - Barry Hashimoto; Sanghoon Park; Victor Y. Wu (Institute for Replication (I4R), 2024)
We computationally reproduce the central findings in Mehmood (2022), which studied the effect of a 2010 reform in Pakistan replacing the presidential appointment of high-court judges with peer appointments. Mehmood leveraged judicial records interpreted and coded by lawyers in Pakistan at the levels of cases, districts, benches, and individual judges. We successfully execute all Stata code in the author's replication archive without any errors, then translate and execute that code in R, again finding no serious errors. Consequently, we reproduce the article's main findings from regressions in Tables 2-4. Additionally, we successfully reconstruct the primary treatment variables of these regressions, after corresponding with the author to clarify precisely how to do so. We then replicate the main findings from regressions in Tables 2-10. Finally, we identify several minor errors which left the article's findings intact. Overall, this report reveals no serious defects in Mehmood (2022). We publicly archive our replication code and a spreadsheet of our results.
Keywords: 330; comparative politics; judicial politics; rule of law; constitutions; replication; computational social science; Pakistan